PP.32.22: CLINICAL USE OF MAGNETIC RESONANCE IMAGING IN EVALUATING OF KIDNEYS AND ADRENALS IN INDIVIDUALS WITH ARTERIAL HYPERTENSION PRACTICING ACTIVE PHYSICAL CULTURE AND SPORTS. (June 2015) - Belichenko, O.; Smolensky, A.; Vorontsov, V.; Averkieva, E.; Vladimirova, V.; Tarasov, A.; Babaeva, .
Abstract : Objective: To study MRI diagnostic possibilities in evaluating of kidneys and adrenals in individuals with arterial hypertension practicing active physical culture and sports. Design and method: MRI was performed in 29 males and 16 females. First group included 26 healthy volonteers (17–29 years old); second group included 19 individuals active physical culture and sports. (17–35 years old). Persons in both groups had normal parameters of blood examination, blood pressure, electrocardiogram, but after exercise stress demonstrated transitory arterial hypertension (AH) 155–170/95–105, and slight proteinyria. Standard MRI included T1, T2-weighted, fat saturation sequences, MRI with contrast enhancement Results: In 4 persons we found solitary serous cists of kidney. In 5 persons MRI revealed different kidney abnormities (aplasia, hypoplasia, dystopia, fused kidney). In 6 persons with normal hormonal parameters and absence of clinical signs, different kinds of adrenal glands pathology were found: adenomathosis (n = 4) and incidentalomas (n = 2, small, inactive tumors with size 9–12 mm). Conclusions: Thus, MRI is a high effective method of evaluation of kidneys and adrenals in individuals with arterial hypertension practicing active physical culture and sports, which is important to find clinically silent changes. These data are necessary in planning training regimen, in decision question of possibility to be involved in different kinds of sport, and prophylactic measures application.